Limited English proficiency and reported receipt of colorectal cancer screening among adults 45–75 in 2019 and 2021 - Jennifer E. Bayly; Shrunjal Trivedi; Kenneth J. Mukamal; Roger B. Davis; Mara A. Schonberg (Preventive Medicine Reports, 2024)
Introduction: Substantial barriers to screening exist for medically underserved populations, especially adults with limited English proficiency (LEP). We examined the proportion of US adults aged 45–75 up-to-date with colorectal cancer (CRC) screening by LEP after 2018. The American Cancer Society began recommending CRC screening for adults 45–49 in 2018. Methods: We analyzed cross-sectional data of adults 45–75 years old participating in the 2019 or 2021 National Health Interview Survey (N = 25,611). Adults were considered up-to-date with screening if they reported any stool test within 1 year, stool-DNA testing within 3 years, or colonoscopy within 10 years. Adults who interviewed in a language other than English were considered to have LEP. Adults not up-to-date with screening were asked if a healthcare professional (HCP) recommended screening, and if so which test(s). Regression models conducted in 2022–2023 evaluated receipt of screening, adjusting for sociodemographics, year, and healthcare access. Results: Overall, 54.0 % (95 % CI 53.1–54.9 %) of participants were up-to-date with screening (9.4 % aged 45–49 vs 75.5 % aged 65–75); prevalence increased from 2019 (52.9 %) to 2021(55.2 %). Adults with LEP (vs English proficiency) were less likely to be up-to-date with screening (31.6 % vs. 56.8 %, [aPR 0.86 (0.77–0.96)]). Among adults not up-to-date, 15.0 % reported their HCP recommended screening (8.4 % among adults with LEP). Conclusions: Nearly half of US adults were not up-to-date with CRC screening in 2019 and 2021 and few reported being recommended screening. Adults with LEP and those 45–49 were least likely to be screened suggesting targeted interventions are needed for these populations.